Republic of Nauru : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Nauru. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
This 2019 Article IV Consultation with Republic of Nauru highlights that it remains vulnerable to climate change and has a narrow economic base and limited capacity. Development challenges are increased by unavailability of land and high incidence of noncommunicable diseases. Growth was stronger than expected in FY2018 but slowed in FY2019. The outlook is subdued, with growth expected to reach 2 percent in the medium term. Revenues are projected to decline, necessitating a fiscal adjustment. Risks are skewed to the downside and include the scaling down of Regional Processing Centre activity and revenues, volatile fishing revenues, climate change, and delays in fiscal and structural reforms. Fiscal adjustment is required to avoid a breach of the fiscal anchor, contain debt, and maintain the Trust Fund contributions. New sources of economic growth and income are needed to support Nauru's development agenda. Policies should be implemented in the near term to support private sector activity, including through financial sector development, state-owned enterprises reform, and land rehabilitation. The effectiveness of education and health spending needs to be improved to meet development goals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet